2015
DOI: 10.1038/srep13790
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Enhanced Hydrophobicity by Atomic-Scale Roughness

Abstract: It is well known that the close-packed CF3-terminated solid surface is among the most hydrophobic surfaces in nature. Molecular dynamic simulations show that this hydrophobicity can be further enhanced by the atomic-scale roughness. Consequently, the hydrophobic gap width is enlarged to about 0.6 nm for roughened CF3-terminated solid surfaces. In contrast, the hydrophobic gap width does not increase too much for a rough CH3-terminated solid surface. We show that the CF3-terminated surface exists in a microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Along the substrate closer to the vapor source of t-F8H2, AFM imaging showed that the surface became rougher and that protuberant circles appeared with increasing sizes, which are the direct evidence of the deposition of t-F8H2. The increasing composition of F 1s and C 1s in XPS analysis and the higher CA of the gradient surface all proved that the density of t-F8H2 molecules increases along the substrate. , It also noted that the more the deposition of t-F8H2, the rougher the substrate; the increase of the roughness may further increase the CA than that of the smooth surface with the same chemical composition. , The presence of the surface roughness may also contribute to the water nucleation and accumulation, considering the trend of the formation of interfacial water droplets; the contribution of the surface roughness compared to that of the surface chemistry is not dominating. The design of a substrate with the same surface chemistry and various roughnesses is worth in-depth investigating.…”
Section: Results and Discussionmentioning
confidence: 87%
“…Along the substrate closer to the vapor source of t-F8H2, AFM imaging showed that the surface became rougher and that protuberant circles appeared with increasing sizes, which are the direct evidence of the deposition of t-F8H2. The increasing composition of F 1s and C 1s in XPS analysis and the higher CA of the gradient surface all proved that the density of t-F8H2 molecules increases along the substrate. , It also noted that the more the deposition of t-F8H2, the rougher the substrate; the increase of the roughness may further increase the CA than that of the smooth surface with the same chemical composition. , The presence of the surface roughness may also contribute to the water nucleation and accumulation, considering the trend of the formation of interfacial water droplets; the contribution of the surface roughness compared to that of the surface chemistry is not dominating. The design of a substrate with the same surface chemistry and various roughnesses is worth in-depth investigating.…”
Section: Results and Discussionmentioning
confidence: 87%
“…For example, the nanogrooves are expected to be used as a hard template for the large-area fabrication of uniaxially aligned metal nanopattern with sub-5 nm scale. Nanopatterned silica surfaces are known to function as a template for metal nanopatterns; therefore, silica nanogrooves are potentially beneficial for preparing high-density sub-5 nm metal nanogaps for strong field enhancements. , In addition, uniaxially aligned nanogrooves can provide surface functions such as orientation control of molecular self-assembly and enhanced hydrophobicity because the surface properties of silica are conveniently well-designed by surface modification. Therefore, the sub-5 nm silica nanogrooves with uniaxial alignment on centimeter-scale substrates will provide benefits for chemistries of nanomaterials and nanoscale interfaces. However, the aligned gratings have a very small aspect ratio, and the slope profile is curved (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of nanopatterns with single-nanometer-scale feature size in a large area is essential for developing electronic devices. The control of sub-5 nm nanopatterns is in demand in the fields of the chemistries of nanomaterials and interfaces. Nanopatterns with sub-5 nm feature sizes afford surface functions such as strong electric-field enhancement , and quantum confinement . The centimeter-scale alignment of sub-5 nm patterns is necessary for the practical application of these functions and for their use as anisotropic surfaces to guide the alignment of soft materials like organic semiconductors and liquid crystals. ,, In general, conventional photolithographic methods exhibit a resolution limit, and the fabrication of sub-10 nm patterns is challenging.…”
mentioning
confidence: 99%
“…1,4,5 In fact, it has been argued that the wetting behavior on rough surfaces can be classified into four classes: Wenzel, Cassie-Baxter, pinning, and hemiwicking state. 11 From theoretical calculations, two special microstructures have been proposed to produce super-hydrophobic states on hydrophilic substrates, as is shown in Figs. 9(a) and 9(b) of the paper by Liu et al 12 However, it is claimed that if the air beneath the water droplet on a sinusoidal substrate is open to the atmosphere, then the superhydrophobic state can exist only when the substrate is hydrophobic.…”
Section: Introductionmentioning
confidence: 99%